CRISPR-mediated genome editing in poplar issued by efficient transformation - Movahedi, Ali; Wei, Hui; Kadkhodaei, Saeid; Sun, Weibo; Zhuge, Qiang; Yang, Liming; Xu, Chen (Frontiers in Plant Science, 2023)
Background: CRISPR has been increasingly used for plant genetic improvements because of its high efficiency and precision. Recently, the authors have reported the possibility of homology-directed repair (HDR) using CRISPR/Cas9 through woody plants such as poplar. HDR is often used for replacing nucleotides with one donor DNA template (DDT), including homologous sequences. Methods: CRISPR-Cas9 has been recruited, and three variables, Agrobacteria inoculator concentration, the ratio of pDDT/pgRNA, and homologous arm length, have been designed to integrate nptII and 2XCamV35S into the MKK2 promoter zone. Results: Here, we showed that recovered poplars on kanamycin-supplemented media exhibited enhanced expression of MKK2 affected by precise integrated 2XCamV35S and nptII, improving biochemical and phenotypic properties. Our findings confirmed that Agrobacterium inoculator OD600 = 2.5, increased DDT numbers during cell division to 4:1 pDDT/pgRNA, and optimized homologous arms 700 bp caused efficient HDR and increased MKK2 expression. Conclusion: Efficient transformations resulted from optimized variables, directly affecting the HDR efficiency through woody plants such as poplar.